Emerging Trends in Rubber Additives for Enhanced Performance and Sustainability - Tejani, Jayadip GhanshyamBhai; Khair, Md Abul; Koehler, Samuel (Digitalization & Sustainability Review, 2021)
This analysis looks into new developments in rubber additives to improve the performance and sustainability of rubber goods. The study is to investigate recycling programs in the rubber industry, assess the applications of multifunctional additives, and investigate advancements in bio-based additives. A thorough evaluation process was used, which included examining peer-reviewed papers, industry reports, and scholarly works about sustainable materials and rubber additives. The key conclusions highlight the revolutionary potential of bio-based additives, like natural antioxidants and plasticizers made from vegetable oil, to lessen environmental effects while preserving or enhancing rubber performance. Multifunctional additives that combine processing, anti-aging, and reinforcing functions optimize rubber characteristics and production efficiency. Policy implications highlight the significance of industry cooperation and regulatory support in overcoming technological obstacles, lowering costs, and encouraging the adoption of sustainable rubber additives. This helps the rubber industry adhere to environmental stewardship and circular economy concepts. The study underscores the significance of developing patterns in rubber additives to propel innovation and sustainability within the rubber materials industry.